Analysis of the Effectiveness of Online Learning Based on Google Classroom on High School Students' Learning Achievement - Doranggi, Selvina; Rizka, Ardiana (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study employs a qualitative descriptive approach using a systematic literature review. Data were collected from scientific journal articles published between 2020 and 2022. The analysis follows the framework of data reduction, data display, and conclusion drawing to synthesize findings on the impact of Google Classroom on students' learning outcomes. Methodology: This study employs a qualitative descriptive approach using a systematic literature review. Data were collected from scientific journal articles published between 2020 and 2022. The analysis follows the framework of data reduction, data display, and conclusion drawing to synthesize findings on the impact of Google Classroom on students' learning outcomes. Main Findings: The findings indicate that Google Classroom significantly enhances students' academic performance, motivation, and engagement. The platform provides flexibility in accessing learning materials, facilitates student-teacher interactions, and supports independent learning. Additionally, Google Classroom fosters active participation, improves discipline in assignment submission, and enhances digital literacy among students. Novelty/Originality of this study: This study contributes to the existing body of knowledge by providing a comprehensive review of Google Classroom's effectiveness in online learning. It highlights the platform's role in fostering student engagement and improving learning outcomes while addressing the challenges of digital education. The findings serve as a valuable reference for educators and policymakers in optimizing online learning strategies.